Neuroprotective and Neuromodulatory Effects Induced by Cannabidiol and Cannabigerol in Rat Hypo-E22 cells and Isolated Hypothalamus - Viviana di Giacomo; Annalisa Chiavaroli; Giustino Orlando; Amelia Cataldi; Monica Rapino; Valentina Di Valerio; Sheila Leone; Luigi Brunetti; Luigi Menghini; Lucia Recinella; Claudio Ferrante (MDPI AG, 2020)
Background: Cannabidiol (CBD) and cannabigerol (CBG) are non-psychotropic terpenophenols isolated from Cannabis sativa, which, besides their anti-inflammatory/antioxidant effects, are able to inhibit, the first, and to stimulate, the second, the appetite although there are no studies elucidating their role in the hypothalamic appetite-regulating network. Consequently, the aim of the present research is to investigate the role of CBD and CBG in regulating hypothalamic neuromodulators. Comparative evaluations between oxidative stress and food intake-modulating mediators were also performed. Methods: Rat hypothalamic Hypo-E22 cells and isolated tissues were exposed to either CBD or CBG, and the gene expressions of neuropeptide (NP)Y, pro-opiomelanocortin (POMC) and fatty acid amide hydrolase were assessed. In parallel, the influence of CBD on the synthesis and release of dopamine (DA), norepinephrine (NE), and serotonin (5-HT) was evaluated. The 3-hydroxykinurenine/kinurenic acid (3-HK/KA) ratio was also determined. Results: Both CBD and CBG inhibited NPY and POMC gene expression and decreased the 3-HK/KA ratio in the hypothalamus. The same compounds also reduced hypothalamic NE synthesis and DA release, whereas the sole CBD inhibited 5-HT synthesis. Conclusion: The CBD modulates hypothalamic neuromodulators consistently with its anorexigenic role, whereas the CBG effect on the same mediators suggests alternative mechanisms, possibly involving peripheral pathways.